Pajak Penghasilan Pribadi: Analisis Bibliometric untuk Penelitian ke Depan - Satriyo Priyo Handoko; Sutopo, Bambang (EKALAYA : Jurnal Ekonomi Akuntansi, 2024)
The application of personal income tax rates in each country in the world varies. Some charge quite high rates, some are moderate, some are small, and there are even countries that don't charge personal income tax. Various factors and reasons lie behind the application of personal income tax rates. In addition, taxes are one of the dominant revenues of a country. In this article, researchers will analyze the distribution and trends of research on Personal Income Tax using the Bibliometric method. This bibliometric study was carried out on the Scopus database. As a result, there are still many opportunities to conduct research on the theme or title of Personal Income Tax.